2007
DOI: 10.1139/a06-007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a change in physical structure and cover on fish and fish habitat in freshwater ecosystems – a review and meta-analysis

Abstract: Aquatic resource managers are continually faced with construction or site development proposals which, if allowed to proceed, would ultimately alter the physical structure and cover of fish habitat. In the absence of clear quantitative guidelines linking the change in habitat to fish, resource managers often use the change in habitat area as a basis for decisions. To assess the weight of scientific evidence in support of management decisions, we summarized both the observational and experimental freshwater fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 301 publications
6
116
0
1
Order By: Relevance
“…For example, reviews of the literature on effectiveness of instream habitat improvement and wood placement have reported significant improvements in physical habitat (pool area and cover) and localized juvenile or adult fish abundance (Roni et al 2002(Roni et al , 2008Smokorowski and Pratt 2007). These studies generally conclude that wood placement leads to physical habitat change, which produced localized increases in fish abundance.…”
Section: Biological Response To Wood Placementmentioning
confidence: 99%
“…For example, reviews of the literature on effectiveness of instream habitat improvement and wood placement have reported significant improvements in physical habitat (pool area and cover) and localized juvenile or adult fish abundance (Roni et al 2002(Roni et al , 2008Smokorowski and Pratt 2007). These studies generally conclude that wood placement leads to physical habitat change, which produced localized increases in fish abundance.…”
Section: Biological Response To Wood Placementmentioning
confidence: 99%
“…Macrophytes can have dramatic effects on the physical structure of aquatic habitats (O'Hare et al, 2006;Smokorowski and Pratt, 2007) and create a heterogeneous mosaic at different scales. Some studies have suggested that structural heterogeneity of macrophytes mediates trophic interactions among various biota (Jeppesen et al, 1997;Pelicice and Agostinho, 2006) and significantly influences the biodiversity of the zooplankton community (Tolonen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…25 Benefits to salmonids have been a primary focus, but benefits to native and non-native species requires evaluation. These structural modifications provide overhanging riparian vegetation, (i.e., shaded riverine aquatic) slower water velocities, and soft bank substrates, which may offer important protective and feeding habitat for migrating juvenile salmon (Murphy and Meehan 1991;Smokorowski and Pratt 2007 Levees that are set back a substantial distance from channels can facilitate restoration of natural riverine processes and provide broad areas of floodplain habitat that benefit aquatic and terrestrial target species (Golet et al 2013). Davenport et al (2016) assessed 15 Delta leveerelated habitat improvement projects.…”
Section: Levee-habitat Projectsmentioning
confidence: 99%